Podobe države in stereotipi, ki jih o Rusiji gojijo učenci ruskega jezika (Country Images and Stereotypes about Russia Held by Russian Language Learners) - Nikitina, L.; Furuoka, F. (Slavistično društvo Slovenije, 2013)
This article explores country images and stereotypes about Russia held by Russian language learners in a big public university in Malaysia. Several studies in the field of applied linguistics have explored language learners’ stereotypes about the target language country. However, there are some gaps in the academic literature on this topic. Firstly, no studies have been done among the learners of the Russian language; secondly, a systematic analysis of cultural stereotypes held by language learners has been lacking. The present study adopts an interdisciplinary approach to address these gaps. It explores the internal structure of the students’ images about Russia, examines the stereotypical images about the country and quantitatively assesses favourability of these stereotypes. The findings show that the images about Russia held by the students clustered around several country-related aspects. Several prominent stereotypes about Russia were distinguished and the majority of these stereotypes were positive. The article concludes with a brief discussion on practical implications of these findings.